Factibilidad para la creación de un complejo ecoturístico en la parroquia Canuto del cantón Chone 2013 - Cusme Vergara, Darwin Lenin (2013)
The thesis entitled Feasibility for Building Complex in the Parish Ecotourism Canton Canute the Chone, is the result of an investigation conducted to tourist sites that exist in our respective areas without quality standards, whose purpose is to satisfy a demand contained in such site. This research seeks to establish the feasibility of creating an ecotourism complex to allow the parish Chone Canton Canute improves e trade and tourism development in the area. Forth e development of this work was used as a tool surveys and statistical graphics that allowed the diagnosis of their alit y of the region and the trade and production situation of the in habitants. It aims to provide a service under quality standards, for that reason we are looking to capture the attention of the in habitants of the parish, county and surround ding are as through advertising campaigns that attract the attention of the same, thus attracting locals and tourists the same to represent in marketing financial benefits, we also determined population levels which provided a general guidance on the target market, which is a fundamental alternative to achieve not only promote the development of the parish and it’s in habitants.